Pharmacokinetics of moxifloxacin in Escherichia coli lipopolysaccharide-induced febrile buffalo calves - PATHANIA, R; SHARMA, S K (The Indian Journal of Animal Sciences, 2010)
Pharmacokinetics and urinary excretion of moxifloxacin was studied in Escherichia coli lipopolyssacharide (1 mg/ kg b.wt.,iv)-induced fever in buffalo calves (n=6). A single intravenous dose of 5 mg/kg body weight was administered in each of the 6 buffalo calves once body temperature was elevated by 1–2°C. Pharmacokinetic analysis of disposition data were best described by 2 compartment open model. The concentration of moxifloxacin in plasma of febrile buffalo calves was detected up to 12 h. The elimination half life and volume of distribution of moxifloxacin after intravenous administration were 2.99±0.10 h and 1.79±0.14 L/kg respectively. The distribution half-life and area under curve (AUC) were 0.09±0.01 h and 12.3±0.76 μg/ml h respectively. The total body clearance (ClB) and tissue:plasma (T:C) ratio were 414.3 ± 24.9 ml/kg/h and 0.22 ± 0.05 respectively. At the end of 24 h, the urinary excretion was approximately 10% of total dose. Using the surrogate marker of AUC/MIC, it was determined that a dosage of 5 mg/kg of moxifloxacin administered by the iv route in febrile buffalo calves is likely to be effective against bacterial isolates with MIC < 0.1 μg/ml.